Renegotiating identity: The cognitive load of evaluating identity and self-presentation after vision loss - Anne E. Ferrey; Lucy Moore; Jasleen K. Jolly (Elsevier, 2024)
When a person is diagnosed with a condition leading to vision loss, life cannot go on as before. As well as developing new ways to manage their daily activities, people must manage the shock to their identity and decide how they now wish to present themselves. These add to the cognitive load of people with who experience vision loss over and above that of their sighted peers. Our qualitative interview study used a thematic analysis to explore the experiences of people with a condition causing vision loss to understand the work they undertook to integrate this diagnosis into their identity (or not) and to decide how and when to communicate their vision loss to others. People often navigated between identities: their identity prior to the diagnosis, and "the blind person" - an identity forced upon them. Linked to this, but a separate task, was deciding how they wished to present themselves to the world - to fully acknowledge their disabilities, to completely cover them, or to choose a path between these extremes. Self-presentation also depended on the audience (family, friends, colleagues, strangers) and this decision was not a single event: most people faced the necessity of repeating this process many times as their vision fluctuated or circumstances changed, and the cognitive effort this required exacted a toll. We build on the work of the disabled identity, identity continuity and self-presentation theory to describe the experiences of people managing their sense of self when faced with the uncertainty of deteriorating vision and deciding how to present themselves to others. This work requires considerable cognitive effort, adding an additional cognitive penalty of disability to those already coping with the practical difficulties of vision loss.